Relative impacts of light, temperature, and reactive oxygen on thaumarchaeal ammonia oxidation in the North Pacific Ocean. (1st September 2017) - Horak, Rachel E. A.; Qin, Wei; Bertagnolli, Anthony D.; Nelson, Alexa; Heal, Katherine R.; Han, Hantten; Heller, Maija; Schauer, Andrew J.; Jeffrey, Wade H.; Armbrust, E. Virginia; Moffett, James W.; Ingalls, Anitra E.; et al.
Abstract: Thaumarchaeota are implicated as the major ammonia oxidizers in the ocean. However, the influence of various abiotic factors in determining their distribution and activity in the upper ocean remain largely unclear. Here, we examined the influence of light, hydrogen peroxide (H2 O2 ), and temperature on ammonia oxidation rates for communities dominated by Thaumarchaeota at the nitrite maximum across two North Pacific transects. In situ ammonia oxidation was almost exclusively driven by Thaumarchaeota, as inferred from ammonia monooxygenase subunit A ( amoA ) genes, amoA transcripts, and inhibitor studies. A major shift in population structure near the eastern North Pacific Subtropical Front was revealed by sequence variation of amoA genes, showing different Thaumarchaeota community structure in oligotrophic gyre and temperate regions. While the most dominant OTUs were closely related, we found significant differences in physiological responses to light and temperature of incubation. At four stations in different biogeochemical regimes, the impact of sunlight intensity and temperature on activity was evaluated using 15 NH 4 + ‐spiked whole seawater collected from the nitrite maximum and incubated at different depths on a free floating in situ array. Ammonia oxidation was usually completely inhibited by PAR at the surface and 21–45% inhibited at 1% surface PAR, whereas a temperature effect on ammonia oxidation was observed at only two of four stations. While inhibition due to H2 O2 cannot be ruled out in surface waters, our findings show that below the mixed layer, photoinhibition, and not H2 O2 toxicity, had a greater influence on ammonia oxidation.